A correction on the paper "A Note on Bi-Periodic Leonardo Sequence'' - Catarino, Paula; Spreafico, Elen
he generating function in Theorem 3 of our work [1] was computedincorrectly. Below we provide the new version of Theorem 3 including thecorrections to be made in its proof. The authors are grateful to Carlos M.Da Fonseca [2] for identifying this error.
Keywords: Mathematics